2009
DOI: 10.1111/j.1475-097x.2008.00852.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nebivolol on blood oxygen transport indices and endothelial dysfunction in patients with arterial hypertension

Abstract: Endothelial dysfunction, which is characterized by impairment of nitric oxide (NO) bioavailability, plays an important role in the development of arterial hypertension. The L-arginine-NO pathway is closely related to oxygen transport to tissue. Endothelial dysfunction in patients with arterial hypertension can affect haemoglobin-oxygen affinity and tissue oxygen supply. Alterations in blood oxygen transport indices may play role in the pathogenesis of arterial hypertension. The aim of the present study was to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 35 publications
0
16
0
1
Order By: Relevance
“…Nitric oxide (NO) -dependent vascular relaxation seems to have a pivotal core role of the insulin-resistant state [25][26]. Various compounds of hemoglobin with NO were previously shown to be positively associated with hemoglobinoxygen affinity of the whole blood, leading to endothelial dysfunction, though the L-arginine-NO pathway [5,19,25,27]. Thirdly, higher serum EPO concentrations may suggest underlying adipose tissue hypoxemia in MS [21,28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nitric oxide (NO) -dependent vascular relaxation seems to have a pivotal core role of the insulin-resistant state [25][26]. Various compounds of hemoglobin with NO were previously shown to be positively associated with hemoglobinoxygen affinity of the whole blood, leading to endothelial dysfunction, though the L-arginine-NO pathway [5,19,25,27]. Thirdly, higher serum EPO concentrations may suggest underlying adipose tissue hypoxemia in MS [21,28].…”
Section: Discussionmentioning
confidence: 99%
“…In the cross-sectional study, we derived patient data from 45,451 Chinese people (27,704 males and 17,747 females) who attended a routine clinical health examination at the First Affiliated Hospital of Wenzhou Medical University between January 2007 and December 2009. Only subjects with no data of components of MS or hemoglobin were excluded.…”
Section: Study Populationmentioning
confidence: 99%
“…The confirmation of this research is found in another investigation, which revealed that antihypertensive treatment with nebivolol that stimulates nitric oxide production, improves endothelium-dependent dilatation and finally improves blood oxygen transport in hypertensive patients. 16 Additionally, mitochondrial function in arterial hypertension is impaired, which contributes to lower oxygen consumption and induces oxidative stress, 17 which also could be the reason for lower peak oxygen uptake in the arterial hypertension population.…”
Section: Physiological Models Of Maximal Oxygen Consumption Limitationsmentioning
confidence: 99%
“…Тому для зменшення симптомів АГ насамперед слід усунути прояви окис ного стресу. Деякі β-блокатори (невібо лол і карведілол) мають здатність збільшувати продукцію NO і покращувати ендотелійзалежне розслаблення, а також зменшувати прояви окисного стресу у пацієнтів з АГ, що може бути основою гіпотензивного ефекту цих препаратів [6,7].…”
Section: вступunclassified